The provisions of honor killings in Islamic law and the Iraqi Penal Code Comparative jurisprudence study - المدرس المساعد محمد شيخان تمرخان (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
This research is comprising of investigation one of the common social phenomena which is murdering by honor killing in Iraq generally and Kurdistan also. Researcher tried to precise discus this phenomenon with identification of Sharia laws and determine the causes and treatment of the subject. This is by explaining some articles which related to that in Islamic sharia and explaining the idea of some Sharia scientists with evidence and different views of them. Then, selecting the right idea compared with the Iraqi criminal law and the. ratio of agreement between sharia and law.